Dynamic capabilities and the ecosystem context of the Scientific and Technological Park at PUCRS - Fagundes, Mara Aparecida Barnaski; Sausen, Jorge Oneide; Vieira, Euselia Paveglio (Revista de Administração da UFSM, 2025)
Purpose: To understand how the development of dynamic capabilities in a science and technology park influenced the trajectory of the smart city movement in an innovation ecosystem from 2002 to 2022. Design/Methodology/Approach: A single case study was used, with a qualitative, exploratory, and descriptive approach, to analyze a science and technology park based on interviews with its coordinators. Findings: The research revealed that the dynamic capabilities of the science and technology park were driven by initiatives for change, innovation, technology acquisition, and process reorganization. These capabilities, in turn, are related to the dimensions of smart cities, manifesting themselves in transformation, multifunctionality, autonomy, management, and processes. Research limitations/Implications: Given the complexity of regional development processes, which involve a series of interconnected variables, the analyses in this study present limitations inherent to this multifaceted nature. Practical implications: The development of dynamic capabilities in the technology park has led to innovative initiatives, contributing to the advancement of the city as a smart model. Social implications: The collaboration between the university, technology park, and city has strengthened the innovation ecosystem, boosting regional development. Originality value: This research presents an original contribution by relating dynamic capabilities to smart cities, opening new perspectives for future investigations and filling a gap in the literature.